Postdevelopmental approaches to pedagogical observation in childhood - Sakr, Mona; Rowsell, Jennifer 1969-; Sherbine, Kortney (Bloomsbury Academic, 2023)
"This book argues that developmental approaches to observation in childhood pedagogy are limiting, restrictive, and present social justice dilemmas. This book unsettles, dismantles, and reimagines observation, proposing new postdevelopmental theories and modes of inquiry for educators. Written by leading scholars based in Australia, Canada, Finland, New Zealand, the UK and the USA, the chapters consider observation as it is enacted in the home, nursery or classroom. Drawing on a range of theories including feminist new materialism, social semiotics, and sociocultural and multimodal approaches to early childhood, the chapters cover a range of areas, from early childhood art and observational literacy tools to intergenerational research, and using photography and video in observations."